2016
DOI: 10.5860/crl.77.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Artists as Scholars: The Research Behavior of Dance Faculty

Abstract: © 2016 Shannon Marie Robinson, Attribution-NonCommercial (http://creativecommons.org/ licenses/by-nc/3.0/) CC BY-NC. The research behaviors and library use of dance scholars are widely unknown, particularly in regard to issues of access to historical materials and new technology preferences. In the past thirty years, college and university dance departments in the United States have developed into independent, research-based programs. Despite the lack of current research examining the information needs of danc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
6
0
6
Order By: Relevance
“…The author also found that musicology, music theory, and composition faculty had the highest levels of library use, followed by music-education faculty. Dougan's findings are supported by those of Shannon Marie Robinson 55 in her interviews with dance faculty. Robinson's study had a small sample size of dance faculty, but the findings were consistent with studies of other performing-arts faculty e.g.…”
Section: The Impact Of Program or Year Of Studymentioning
confidence: 61%
“…The author also found that musicology, music theory, and composition faculty had the highest levels of library use, followed by music-education faculty. Dougan's findings are supported by those of Shannon Marie Robinson 55 in her interviews with dance faculty. Robinson's study had a small sample size of dance faculty, but the findings were consistent with studies of other performing-arts faculty e.g.…”
Section: The Impact Of Program or Year Of Studymentioning
confidence: 61%
“…A strong and consistent source of information for the participants in this study was through informal information sharing with their peers both within specific faires and within their craft, echoing IB research with other performers (Robinson, 2016). John Ringo explained that Every few years or so, I'll go to a juggling convention.…”
Section: Rq2 How Do Other Information Behavior Theories Explain the I...mentioning
confidence: 67%
“…Kahn (1994) explored the research needs of theater artists and how this research was embedded into the text and context of a play. Robinson (2016) explored the research practices of dance faculty in US colleges and universities and found that their practices were similar to those found in research with theater professionals. In particular, the dance faculty “value face-to-face discussions with their peers and often rely on this network to provide recommended reading” (Robinson, 2016, p. 789).…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…Egyértelműen látszott, hogy a publikált kutatások több, mint 70%-a angol anyanyelvű országokból származott, ezen belül több, mint 60% (n = 26) az Egyesült Államokból (Baran, 2020;Bonner, 2022;Brown, 2022;Clendinning, 2022;Conner et al 2021;DiPasquale et al, 2021;DiPasquale & Roberts, 2022;Risner & Musil, 2017;Dragon, 2015;Duffy, 2015Duffy, , 2019Duffy, , 2020Gail et al, 2018;Haines & Torres, 2016;Johnson, 2018;Kearns, 2016;Lopez, 2019;McCarthy-Brown, 2015;Patton et al, 2022;Pulinkala, 2014;Purvis, 2018;Risner & Barr, 2015;Robinson, 2016;Sulé, 2015;Walker, 2019) és az Egyesült Királyságból (n = 17) (Assandri, 2019;Domene & Morley, 2022;Dryburgh, 2020;Dryburgh & Jackson, 2016;Ehrenberg, 2020;Farrer, 2018;Higdon & Stevens, 2017;Johnson et al, 2019;Kelsey & Uytterhoeven, 2016;Mills, 2014;O'Leary et al, 2019;Petsilas et al, 2019;Rimmer, 2017;Ritchie & Brooker, 2018Roe, 2017;Seago, 2020), míg csak a cikkek mindössze 10,14%-a származott Ausztráliából…”
Section: A Tánccal Kapcsolatos Felsőoktatási Kutatások Földrajzi Elos...unclassified